RECYCLED CONCRETE - ECOLOGY AND ECONOMIC CRITERIAS - Curovic, Nada (Journal of Applied Engineering Science, 2016)
Recycled concrete is a relatively new technology in the production of concrete, and as such it requires careful approach. Only proper scientific research and proven professional guidelines should govern the development of this technology. Recycling of this material, which is the symbol of construction today, becomes not only technical innovation, but also the needs of modern urban society. The paper presents basic ecology and economic criteria about use of recycled aggregates in concrete production. Some advantages of these materials are also presents. An accent is given to that we need to start thinking about our environment.
Keywords: environment; economy; recycling; ecology; Concrete